IMPLEMENTASI KEBIJAKAN KEWASPADAAN DINI DI PERBATASAN NEGARA RI-RDTL : (Studi pada Kabupaten Belu Tahun 2020) - Frengky Mone Adoe Kadji (Jurnal Administrasi Publik, 2022)
This study aims to analyze the implementation of early warning policies in Belu Regency, which is analyzed based on the implementation theory of Van Meter and Van Horn (1975), with six factors that influence the implementation of a policy, namely: size and objectives, resources, characteristics of implementing agents, communication between organizations and implementing activities, attitudes of implementers and the social, economic and political environment of the policy. This study uses descriptive qualitative research methods to identify the extent to which the policy is implemented. Based on the results of the study, was found that the implementation of the early warning policy in Belu Regency in accordance with the Belu Regent's Decree Number 42 of 2020 concerning the Establishment of the Belu Regency Government's Early Warning Team in 2020, has not been optimally implemented, that can be seen from the communication, coordination and cooperation that has been carried out, developed so far which is still limited, and the continuity of reports and recommendations resulting from the policies implemented in Belu Regency.